Ballast optimizing to agricultural tractor Agrale-Deutz BX 4.150 - Corrêa, Ila Maria; Maziero, José Valdemar G.; Bertella, Odi; Morello, Marcos; Yanai, Kiyoshi (Pesquisa Agropecuaria Brasileira, 1997)
The total weight and the axle load of front-wheel drive tractors are important in the optimizing of their drawbar performance. In this paper, the objective was to select a load condition that improve the tractive performance of tractors, with a decreasing of ballast when compared to maximum ballast limited to 82 kg/kW for the engine. The analytical comparison between tractive coefficient values associated with the other parameters obtained on concrete and field surfaces allows us to conclude that the Agrale Deutz BX 4.150 may be used with total weight in the range of 73.7 to 75.7 kN, which represents a reduction of 5.9 kN when compared to the maximum permissible ballast with an axle load distribution between 38.0% to 42.7% (average 39.9%) of the total weight on the front axle. Under this condition, the tractive performance was considered satisfactory when compared to maximum ballast.